Meta-Analysis and Systematic Review of the Predictive Value of Carotid Plaque Hemorrhage on Cerebrovascular Events by Magnetic Resonance Imaging - Saam, Tobias; Hetterich, Holger; Hoffmann, Verena; Yuan, Chun; Dichgans, Martin; Poppert, Holger; Koeppel, Thomas; Hoffmann, Ulrich; Reiser, Maximilian F.; Bamberg, Fabian (Journal of the American College of Cardiology, 2013)
This study sought to conduct a systematic review and meta-analysis to determine precise estimates of the predictive value of carotid intraplaque hemorrhage (IPH) as determined by magnetic resonance imaging (MRI) for cerebrovascular events. There is emerging evidence that MR-based carotid atherosclerotic plaque assessment identifies high-risk features associated with cerebrovascular events. However, available data are based on smaller samples with heterogeneous source populations despite a promising value for noninvasive risk stratification. We searched PubMed, EMBASE, and the Cochrane Library through September 2012 for studies that followed >35 individuals after baseline MRI. Independent observers abstracted information on populations, MR techniques, outcomes, and study quality. Risk estimates of the presence of IPH for cerebrovascular events were derived in random effects regression analysis, and causes of heterogeneity were determined in meta-regression analysis. We identified 8 eligible studies including 689 participants who underwent carotid MRI. The prevalence of IPH at baseline was high (49.0%). Over a median follow-up of 19.6 months, a total of 108 cerebrovascular events occurred (15.7% event rate). The presence of IPH was associated with an ∼6-fold higher risk for events (hazard ratio [HR]: 5.69; 95% confidence interval [CI]: 2.98 to 10.87). The annualized event rate in subjects with detectable IPH was 17.71% compared with 2.43% in patients without IPH. Meta-regression analysis showed symptomatic subjects had higher risks as compared with asymptomatic subjects (HR: 11.71, 95% CI: 5.17 to 26.48 vs. HR: 3.50, 95% CI: 2.59 to 4.73, p = 0.0065), Also, differences were observed for sex and sample size (all p < 0.01), with moderate visual publication bias due to missing smaller sample-size studies (p = 0.18). Presence of IPH on MRI strongly predicts cerebrovascular events. Homogenization of future studies is warranted to allow for sufficient assessment of level of evidence for intervention trials.